2022
DOI: 10.3389/fphar.2022.911140
|View full text |Cite
|
Sign up to set email alerts
|

Three main metabolites from Wolfiporia cocos (F. A. Wolf) Ryvarden & Gilb regulate the gut microbiota in mice: A comparative study using microbiome-metabolomics

Abstract: Wolfiporia cocos (F. A. Wolf) Ryvarden & Gilb, also known as Poria cocos is an ancient edible and medicinal mushroom that has been valued for thousands of years for its tranquilizing, diuretic, and spleen-enhancing properties. Because of the mushroom’s complex composition, its pharmacological effects have not been fully clarified. Therefore, to expand our knowledge of these effects from a pharmacological perspective and exploit potential medicinal value of fungal mushroom, we extracted three main metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Furthermore, our previous report suggests that PCP can effectively modulate GM and act as a prebiotic agent in mice [ 23 ]. In line with our study, a recent study also found that main metabolites of PC significantly altered the gut microbiota and the intestinal metabolites in mice [ 30 ]. Besides modulating the dysbiosis in the alcoholic hepatic steatosis mouse model, PCP also alleviated liver symptoms by inhibiting the ethanol-induced fungal overgrowth [ 31 ].…”
Section: Introductionsupporting
confidence: 92%
“…Furthermore, our previous report suggests that PCP can effectively modulate GM and act as a prebiotic agent in mice [ 23 ]. In line with our study, a recent study also found that main metabolites of PC significantly altered the gut microbiota and the intestinal metabolites in mice [ 30 ]. Besides modulating the dysbiosis in the alcoholic hepatic steatosis mouse model, PCP also alleviated liver symptoms by inhibiting the ethanol-induced fungal overgrowth [ 31 ].…”
Section: Introductionsupporting
confidence: 92%
“…In addition, mushroom polysaccharide, such as that of Poria cocos , has been demonstrated to promote the enrichment of norank_f__Muribaculaceae in mice. 22 Moreover, the relative abundance of Akkermansia in the Control group was 25.76%, which almost disappeared in the Model group (0.24%). After 5-ASA, ABP, ABP-1, and ABP-2 treatments, its relative abundance increased to 13.74%, 14.46%, 18.93%, and 20.26%, respectively (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Commensal bacteria, probiotics, and pathogens coexist in the gut, and the balance of intestinal microbiota is essential for host health, while their imbalance is associated with the development of diseases, such as enteritis. 22 Modulating the intestinal microbiota is an important strategy for improving health and preventing or treating disease. Prebiotics, for instance, cannot be digested by human alimentary enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction and purification of PCY was performed according to a specific method that refers to our previous study [ 18 ]. The PMP (1-phenyl3-methyl-5-pyrazolone) pre-column derivatization-HPLC method was applied to analyze the monosaccharides of PCY, and the structure was applied scanning electron microscope (SEM) to observe.…”
Section: Methodsmentioning
confidence: 99%
“…Modern pharmacological studies have shown that polysaccharides extracted from P. cocos have good biological activities such as anti-tumor, immunomodulation, hypoglycemia, lipid regulation and liver protection [ 15 , 16 , 17 ]. Our group previously studied the effect of three main active ingredients from P. cocos on mice and found that PCY can increase the number of Lactobacillus to regulate the gut microbiota, which is beneficial to the health of the organism [ 18 ]. Fungal polysaccharides from medical and edible mushroom sources have great prebiotic potential and are expected to be used to alleviate antibiotic-associated diarrhea, which deserves to be explored in depth.…”
Section: Introductionmentioning
confidence: 99%